Investigation of influence of adjustments in cyclist arm position on aerodynamic drag using computational fluid dynamics - Giljarhus, K. E. T.; Stave, D. Å.; Oggiano, L. (Proceedings, 2020)
In professional cycling, even small adjustments in position could mean that valuable seconds are gained over the course of a time-trial race. This study investigates the influence of arm position on the aerodynamic drag of a cyclist. Based on a 3D scanned model of a professional cyclist, 64 alternate positions are generated. The parameters that are investigated are the distance between elbows, elbow extension, and distance between hands. Computational fluid dynamics (CFD) simulations of all positions are performed, and a regression model is built from the results. The results indicate that the optimal posture is achieved for a minimum in all investigated parameters, which means that the hands and elbows should be kept together with hands up towards the face. Furthermore, elbow extension seems to be the most crucial parameter, followed by the distance between elbows, and then by the distance between the hands. The presented methodology can be applied to study other parameters relevant to cycling aerodynamics or be applied to other sport activities as well.